Preventive effects of melatonin and amifostine on irradiated rats with experimental periodontitis - Nur Yorgancilar; Oguz Kose; Sema Yilmaz Rakici; Tolga Mercantepe; Kerimali Akyildiz; Levent Tumkaya; Adnan Yilmaz (BMC Oral Health)
Abstract Background The aim of this study was to investigate the preventive effects of amifostine and melatonin oxidatively, biochemically and histomorphometrically in rats with radiotherapy-induced experimental periodontitis. Methods 40 female Sprague-Dawley rats were divided into 5 groups: Control, experimental periodontitis (Ep), Ep + radiotherapy (Ep + Rt), Ep + Rt + amifostine (Ep + Rt + Ami), Ep + Rt + melatonin (Ep + Rt + Mel). The day after induction of periodontitis by ligature, a single dose of 5 Gy radiotherapy was administered. On the same day, treatments with amifostine (200 mg/kg) for 3 days and melatonin (10 mg/kg) for 15 days were started. By after 23 days of experiment, periodontal bone loss was measured by histomorphometry. RANKL, OPG and Caspase-3 activities were analyzed immunohistochemically and inflammatory cytokine (IL-1β, IL-10, IL-6, TNF-α) levels and oxidative stress (TOS/TAS) were analyzed biochemically in tissue homogenates. Results It was observed that there was a significant difference in many biochemical parameters and oxidative stress levels between the control group and Ep + Rt (p < 0.05). Alveolar bone destruction in the melatonin prophylaxis group was observed to be close to control (p > 0.05). Melatonin significantly improved biochemical, histochemical, apoptotic and bone loss levels in irradiated experimental periodontitis rats (p < 0.05). When comparing the two drug groups (Ep + Rt + Ami and Ep + Rt + Mel), no statistically significant difference was found at any parameter level (p > 0.05). Conclusion Both melatonin and amifostine can significantly limit RT-induced periodontal bone loss by suppressing inflammatory stress, apoptotic mechanisms, and RANKL-related osteoclastic activity. Given the limited side effects of melatonin, it may be an alternative to amifostine.